Studies on solid phase synthesis,characterization and fluorescent property of the new rare earth complexes - Jianwei SHI; Xiaoxu TENG; Linling WANG; Rong LONG (Journal of Hebei University of Science and Technology, 2015)
Rare earth-β-diketone ligand complex luminescent material has stable chemical properties and excellent luminous property. Using europium oxide and (γ-NTA) as raw materials, novel rare earth-β-dione complexes are synthesized by solid state coordination chemistry. The synthesis temperature and milling time are discussed for optimization. Experimental results show that the suitable reaction situation is at 50 ℃ and 20 h for solid-phase synthesis. The compositions and structures of the complexes are characterized by means of elemental analysis, UV-Vis and FTIR methods, and the phase stability of the complex is determined by using TG-DTA technique. It is proved that preparation of waterless binary rare earth complexes by the solid phase reaction method results in a higher product yield. The fluorescence spectra show that between Eu (Ⅲ) and γ-NTA, there exists efficient energy transfer, and the rare earth complexes synthesis is an excellent red bright light-emitting material with excellent UV excited luminescence properties.